THE TEACHING OF CRITICAL READING IN AN EFL CLASSROOM - Lestari, Zubaedah Wiji (PEOPLE: International Journal of Social Sciences, 2015)
This study exposes the process of teaching critical reading in an EFL classroom in one public senior high school in Bandung, Jawed Barat, Indonesia. This study was conducted as an effort to help students to develop their critical reading. The teaching of critical reading in senior high school level is considered very potential in that the students face a lot of choices of sources of information and that they will face a lot of more reading material at the higher level college. This study used a qualitative method in the form of case study design. The data were obtained from several sources; those are field notes, classroom observations, student’s journal, group interview, and questionnaire in the end of teaching program. The finding reveals that the teaching of critical reading to some extent may increase students’ critical reading skills. With the reference to the finding, it is recommended that critical reading be taught in the senior high school level with some modification to the material used in the classroom and better classroom management. Further, research on critical reading is widely open in other content subjects, and in other language skills.